Electroacupuncture Pretreatment Prevents Cognitive Impairment Induced by Cerebral Ischemia–Reperfusion via Adenosine A1 Receptors in Rats - Shi, Yiyi; Dai, Qinxue; Ji, Binbin; Huang, Luping; Zhuang, Xiuxiu; Mo, Yunchang; Wang, Junlu (Frontiers in Aging Neuroscience, 2021)
Previous study demonstrated that pretreatment with electroacupuncture (EA) induces rapid tolerance to focal cerebral ischemia. The present study we investigated whether adenosine receptor 1 (A1 R) is involved in EA pretreatment induced cognitive impairment after focal cerebral ischemia in rats. Two hours after EA pretreatment, focal cerebral ischemia was induced by middle cerebral artery occlusion for 120 minutes in male Sprague-Dawley rats. The neurobehavioral score, cognitive function (as determined by the Morris water maze test), neuronal number, the Bax/Bcl-2 ratio was evaluated at 24 hours after reperfusion in the presence or absence of CCPA (a selective A1 receptor agonist), DPCPX (a selective A1receptor antagonist) into left lateral ventricle or A1 short interfering RNA into hippocampus area. The expression of A1 receptor in the hippocampal was also investigated. The result shown that EA pretreatment upregulated the neuronal expression of A1 receptor in the rat hippocampus at 90 min. And EA pretreatment revered cognitive impairment, improved neurological outcome, and inhibited apoptosis at 24 hours after reperfusion. Pretreatment with CCPA could imitate the beneficial effects of EA pretreatment. But the EA pretreatment effects were abolished by DPCPX. Furthermore, A1 receptor protein was reduced by A1 short interfering RNA attenuated EA pretreatment-induced cognitive impairment.